Introduzione alle lingue storiche minoritarie nell’Italia meridionale, in Sardegna e in giro per l’Italia - Autelli, Erica; Caria, Marco; Imperiale, Riccardo (Linguistik Online, 2025)
Italy is a territory rich of different cultures, identities and languages – the latter unfortunately arbitrarily acknowledged as such by the national law 482/1999 (e. g. also Orioles 2003; Toso 2008, the latter recently summarized in Autelli/Caria 2024). In this special issue such language varieties will be describing, shifting from those to be found in the Southern part of Italy and Sardinia to those of the Roms and Sintis spread through the whole Italian peninsula, dealing both with the history of a certain language variety and its linguistic feateures and to the measures untertaken by the state and by the different associoations and research centres to help preserve them.